2009
DOI: 10.1007/s11144-009-0015-3
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic activity of N-doped TiO2: photocatalytic synthesis of o-aminophenol at room temperature

Abstract: The photocatalytic synthesis of o-aminophenol in methanol was investigated with N-doped TiO 2 nanoparticles under UV-light irradiation. The catalytic quantities of N-doped TiO 2 prepared by a simple modified sol-gel process with urea as nitrogen source rapidly reduced o-nitrophenol to the corresponding amine at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The peak of binding energy of N is mainly at 400.0 eV, and the peak at 397.8 eV is relatively small. The binding energy at 397.8 eV indicates that the nitrogen atom in the form of beta-N ( β -N) exists in the crystal, and that at 400.0 eV indicates that the nitrogen atom in the form of gamma-N ( γ -N) exists in the crystal or in the form of N-N and N-O bond [ 44 ]. Similarly, according to the Lorentz fitting results of the N1s peak, the ratio of β -N to γ -N in the films deposited under the conditions of r = 1/1 and r = 1/3 is estimated to be 2.68 and 2.03, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The peak of binding energy of N is mainly at 400.0 eV, and the peak at 397.8 eV is relatively small. The binding energy at 397.8 eV indicates that the nitrogen atom in the form of beta-N ( β -N) exists in the crystal, and that at 400.0 eV indicates that the nitrogen atom in the form of gamma-N ( γ -N) exists in the crystal or in the form of N-N and N-O bond [ 44 ]. Similarly, according to the Lorentz fitting results of the N1s peak, the ratio of β -N to γ -N in the films deposited under the conditions of r = 1/1 and r = 1/3 is estimated to be 2.68 and 2.03, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The critical load of WO 3 /S-N-TiO 2 is close to that of WO 3 /TiO 2 since both coatings possess alike interface properties stemming from the hybrid structure of TiO 2 and WO 3 . It seems that S, N co-doped TiO 2 enhances the interface adhesion due to the densifying layer resulting from crystalline refinement of doped TiO 2 , the N, S co-doped TiO 2 has a larger specific surface area [15] than pure TiO 2 , the huge surface energy is helpful for the improvement of interface adhesion. It can also be concluded that the added transitional layer increases the total coating thickness and accordingly strengthen the adhesion with respect to unitary TiO 2 coating.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the current industrial hydrogenation processes have some disadvantiges, such as high temperature (vapor-phase processes) and toxic, flammable, environmentally hazardous organic solvents (liquid phase processes). Great efforts have been made to develop a greener hydrogenation catalyst and more cost-effective processes, and numerous methods for the reduction of aromatic nitro have been reported in the literature, such as catalytic hydrogenation, catalytic transfer hydrogenation, CO/H 2 O conditions, and other reduction systems; however, the problems remain unsolved. Therefore, the development of more effective, less toxic, and handle-convenient catalysts for this transformation is still highly desirable.…”
Section: Introductionmentioning
confidence: 99%